Gandhi’s Ideas of Women in Hinduism - Ida Rosyidah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
Similar to Eastern philosophers, Gandhi also perceived differences between men and women. According to Gandhi, women are often marginalized while men play significant and dominant roles over women. In a patrilineal society, men are always prioritized, not only within the family but also in religious rituals. The same is found in Hinduism, where men hold more prominent roles in religious ceremonies. However, Gandhi’s thoughts are not detached from the Hindu teachings they use as guidance in daily life.